2017
DOI: 10.3201/eid2304.161399
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Initial Analysis of a Laboratory-Based Weekly Biosurveillance System, Provence-Alpes-Côte d’Azur, France

Abstract: We describe the implementation of an automated infectious disease surveillance system that uses data collected from 210 microbiologic laboratories throughout the Provence-Alpes-Côte d’Azur region in France. Each week, these facilities report bacterial species that have been isolated from patients in their area. An alarm is triggered whenever the case count for a bacterial species infection exceeds 2 SDs of the historical mean for that species at the participating laboratory. At its inception in July 2013, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Furthermore, they warrant the implementation of new technology-based diagnostic tests, approaches and strategies [12] , [54] , [55] , including culturomics, proteomics and genomics, to detect known infectious agents and discover new ones. Moreover, real-time surveillance tools, including some based on microbiology laboratory data such as those set up by our institution in southeastern France and in sub-Saharan Africa, deserve implementation [5] , [56] . Finally, the exploration of the microbiota and its relationships with dietary patterns is another important research field being explored at the Institut Hospitalo-Universitaire Méditerranée Infection [57] , [58] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they warrant the implementation of new technology-based diagnostic tests, approaches and strategies [12] , [54] , [55] , including culturomics, proteomics and genomics, to detect known infectious agents and discover new ones. Moreover, real-time surveillance tools, including some based on microbiology laboratory data such as those set up by our institution in southeastern France and in sub-Saharan Africa, deserve implementation [5] , [56] . Finally, the exploration of the microbiota and its relationships with dietary patterns is another important research field being explored at the Institut Hospitalo-Universitaire Méditerranée Infection [57] , [58] .…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, such infections have been suspected several times. In 2015, our laboratory data–based surveillance system, PACASurvE (Provence-Alpes-Côte d’Azur Surveillance Epidemiologic System) [5] , detected several consecutive abnormal increases in the number of Enterococcus faecalis infections, especially community-acquired urinary tract infections, in different areas of the Provence-Alpes-Côte d’Azur French region [6] . Investigations led us to strongly suspect a zoonotic origin for the outbreak, with chicken-based food as a vehicle for the pathogen.…”
Section: Bacteriamentioning
confidence: 99%
“…This disparity between reality and the myth of antibiotic resistance could only be resolved by implementing efficient antibiotic resistance surveillance systems that observe in real or nearreal-time the results of susceptibility testing in deceased and survivors patients, as it is already the case in our institution 6 . Therefore, at the Marseille University Hospital Institute, using the monitoring systems implemented BALYSES (Bacterial real-time Laboratory-based Surveillance) 15 , MARSS (Marseille Antibiotic Resistance Surveillance System) and PACASurvE (PACA Surveillance Epidemiologic System) 16 , we monitor weekly the results of all strains isolated in the 4…”
Section: Introductionmentioning
confidence: 99%
“…University Hospitals of Marseille (Assistance Publique Hôpitaux de Marseille) and in laboratories of the region which participate to this surveillance system for which antibiotic susceptibility testing (AST) results are available 6,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the benefit of laboratory surveillance and its capability to accurately detect influenza outbreaks earlier than syndromic surveillance. [3][4][5][6][7][8][9] Current laboratory surveillance has an approximately 4-week lag due to laboratory test turn-around time, data collection and data analysis. As part of strengthening influenza virus surveillance in response to the 2009 influenza A (H1N1) pandemic, the real-time laboratory-based influenza surveillance system, the Bangkok Dusit Medical Services Surveillance System (BDMS-SS), was developed in 2010 by the Bangkok Health Research Center (BHRC).…”
mentioning
confidence: 99%